Bringing Color into the Living Room: Analyzing TV Guide Covers, 1953 to 1997 - Upright, Craig (TRAILS: Teaching Resources and Innovations Library for Sociology, 2015)
Many contemporary students are unfamiliar with the cultural history of television programming in the United States. References to iconic series that represented significant milestones in minority representations and discussions of racial issuessuch as I Spy, Julia, All in the Family, or even The Cosby Showfail to serve as useful examples when instructors cannot assume widespread familiarity. The exercise described in this note uses cover images from the magazine TV Guide between 1953 and 1997 to illustrate changing representation of minorities, present an overview of television programming history, and provide an opportunity to apply theoretical insights. Using a web-based archive of the magazine covers, the students can observe the emergence of nonwhite entertainers not only on the television screens but also onto the coffee tables of mainstream American families. This exercise can precede several discussions about racial issues, such as minority representation, cultural reflection, or post-civilrights-era history.